Ready To Be A Blood Hero: Edukasi Kemanusiaan dan Gerakan Solidaritas - Sukmawati, Sukmawati; Nurhakim, Furkon; Mamuroh, Lilis; Kosim, Kosim (Universitas Nurul Jadid, 2025)
Humanitarian action is a tangible manifestation of social awareness aimed at fostering solidarity among community members. The